Association of Mental Health Problems and Socio-Demographic Factors Among Adolescents in Indonesia - Veranita Pandia; Anindita Noviandhari; Indah Amelia; Galih Hafidz Hidayat; Eddy Fadlyana; Meita Dhamayanti (SAGE Publishing, 2021)
Mental health in adolescents represent a considerable public health issue in developing countries. These problems are considered a source of problem for adolescents' quality of life. The study objective was to determine the association between mental health problems and sociodemographic variables among adolescents. A cross-sectional study was conducted from October to December 2016 using a school-based survey in 4 districts and 3 cities in West Java Province, Indonesia. Stratified multistage random sampling was used to select junior and senior high school students and self-administered questionnaires were used to collect study data which included: personal data, socioeconomic status scale, and self-reported version of Strengths and Difficulties Questionnaire (SDQ) which divided into 5 subscales. About 3452 adolescents of 32 schools were included in this study, 59% female, 56% junior high school, 56% district residence, most parents' education were senior high school. The prevalence of mental health problems based on SDQ subscale as total difficulties, conduct problem, emotional symptoms, peer problems, hyperactivity-inattention, were abnormal 31.6, 38.9, 30, 29.3, 15.6, respectively. Mental health problems were more prevalent amongst adolescents in junior high school and residence in district area, with RR and 95% CI were 1.14 (1.04-1.26), and 1.18 (1.08-1.30). As conclusions mental health problems in adolescents were associated with education level and residence area